Reforming the Islamic Calendar and Religious Authority: Dynamics of Hijri Calendar Calculation in Indonesia within Persatuan Islam's Thought - Marwadi; Labib, Mughni; Zain, Muhammad Fuad (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
Differences in determining the start of Hijri calendar months, particularly Ramadan, Shawwal, and Zulhijah, remain a recurring issue in Indonesia due to the persistent divide between users of hisab (astronomical calculations) and rukyat (moon sightings), each adhering to different criteria without a shared standard. This study offers a novel examination of Persatuan Islam (Persis), a prominent Islamic organization historically aligned with hisab, which has now shifted its stance by integrating rukyat into its calculations. Using a qualitative library research approach, the study draws on documentation and interviews, analyzed through the lenses of the philosophy of science and sociology of knowledge, to understand this paradigm shift. The findings show that Persis has transitioned to a hisab cum rukyat method, a hybrid approach combining calculations with empirical observation. This methodological innovation marks a significant development in Indonesia's Hijri calendar discourse. The research highlights this evolving paradigm as a promising alternative for bridging the long-standing divide and fostering the potential unification of the Hijri calendar in Indonesia.